TANTANGAN PUNGLI DI JAWA BARAT: MASIH PERLUKAH KEBERADAAN SATUAN TUGAS SAPU BERSIH PUNGUTAN LIAR (SATGAS SABER PUNGLI) ? - Rusman Rusman; Hilman Nur; Ashraf Firmansyah (Universitas Suryakancana, 2023)
Protecting every citizen from the threat of crime is a basic duty of the State. Such is the case with the threat of illegal levies that always threaten the community in carrying out social life. Therefore, the government formed a Clean Sweep Illegal Levy Task Force (hereinafter referred to as the Satgas Saber Pungli) as a manifestation of the State's duty to answer public unrest. West Java Province itself through the Satgas Saber Pungli Provinsi Jawa Barat (hereinafter referred to as Satgas Saber Pungli Prov. Jabar) as an extension of the task of the Saber Pungli Task Force at the Provincial level which has been established since the end of 2016. This paper discusses the existence of an institution that combats illegal levies. Through this paper, there are findings related to the success of the institution enforcing the crime of illegal levies with several notes that are expected to be an evaluation for related institutions. The approach to the problem that will be used in this paper is normative juridical by using literature data or secondary data. In addition, this paper uses quantitative data analysis as a reference material to answer existing questions. This research uses this data which is then examined based on legal rules, laws and regulations and legal concepts related to this paper. Keywords : Crime of Illegal Levy, Threat to Society, Clean Government.